From generation to generation : the health and well-being of children in immigrant families - Hernandez, Donald J. (Donald James), 1948-; Charney, Evan (National Academy Press, 1998)
From Generation to Generation explores what we know about the development of white, black, Hispanic, and Asian children and youth from numerous countries of origin. Describing the status of immigrant children and youth as "severely understudied," this work both draws on and supplements existing research to characterize the current status and outlook for immigrant children. The book discusses the many factors - acculturation, conditions in their receiving communities, parent employment and income, fluency in English, delivery of health and social services, and public policies - that shape the lives of these children and youth. The committee makes recommendations for improved research and data collection designed to advance knowledge about these children and, as a result, their visibility in current policy debates